Szabad lesz, bíró úr? avagy a laikus bíráskodás jogelméleti/ jogszociológiai kérdései - Budea Cintia (Acta Universitatis Szegediensis : forum : publicationes discipulorum iurisprudentiae, 2023)
My research focuses on the legal theoretical and socio-legal examination of fundamental issues related to lay adjudication, with special emphasis on the Hungarian lay judge system. At the core of this research is the exploration of reasons behind the limited application of lay elements and the identification of dilemmas associated with the legal institution, aiming to propose a potential direction for its further development, while also meeting the demand for professionalization. To accomplish this, I consider it essential to analyze societal factors that could influence the success (or lack thereof) of the lay adjudication system. The timeliness of the topic is evident in the persistent critique concerning the administration of justice, often summarily stating that the courts provide „mere” legal services instead of dispensing justice. This suggests a waning societal trust in the justice system, and the restoration of which could potentially be achieved through a well-chosen lay adjudication mechanism aligned with the (societal) expectations of the 21st century, even if Western legal systems, due to the reluctance of professionalized legal practitioners, increasingly provide less room for such systems. The efficient administration of justice carried out exclusively by professional judges frequently appears incompatible with lay court models that aspire to representativeness. However, through an analysis of various Hungarian and foreign literature syntheses and public legal consciousness measurements, I have concluded that lay adjudication in our country requires a reform that can moderate doubts about the institution’s legitimacy by strengthening the professional aspects of lay participation. Consequently, I have determined that the requirement of public participation need not be dismissed in our current era; rather, the implementation of this principle should be adjusted to changing societal expectations and circumstances.